Not that innocent – ammonium ions boost homogeneous light-driven hydrogen evolution. Issue 29 (21st March 2022) - Heiland, Magdalena; De, Ratnadip; Rau, Sven; Dietzek-Ivansic, Benjamin; Streb, Carsten
Abstract : Catalytic and photophysical studies provide initial information on the general hydrogen evolution reactivity enhancement by ammonium ions (NH4 + ). Abstract : We report that the homogeneous light-driven hydrogen evolution reaction (HER) can be significantly enhanced by the presence of seemingly innocent ammonium (NH4 + ) cations. Experimental studies with different catalysts, photosensitizers and electron donors show this to be a general effect. Preliminary photophysical and mechanistic studies provide initial suggestions regarding the role of ammonium in the HER enhancement.